Effect of Crosslinking on Control Drug Release of Hydroxychloroquine sulphate drug-using Alginate beads - S. Giridhar Reddy (Iranian Journal of Materials Science and Engineering, 2022)
Sodium alginate (SA), brown seaweed algae, and Lignosulphonic acid (LS), a plant product, are biodegradable polymers extensively investigated for drug-controlled release. The Hydroxychloroquine sulphate (HCQ) drug, an antimalarial drug, was extensively used in the initial periods of COVID situations. The HCQ drug release from SALS beads is investigated for its control release in a simulated medium (pH1.2 and pH7.4) using different crosslinking agents such as Calcium chloride, Barium chloride and Aluminum chloride. The HCQ release has better controlled in Barium crosslinked beads. They are found to be relatively intact and stable and release the drug for more than 180 minutes in the simulated medium. Further drug entrapment studies prove very high for Ba crosslinked SALS beads. Whereas Aluminum crosslinked beads showed, inferior crosslinking and drug retention in beads is very low and starts degrading in simulated fluids. Drug release kinetics were analyzed using various kinetic model equations to discuss the order of reaction and drug-polymer mechanism.  FT-IR investigations of beads show chemical interactions between crosslinking ion and alginate blends.